Pendidikan Agama Islam Dan Budaya Digital: Menjaga Identitas Budaya Lokal Di Era Global - Ardillah, Ardillah (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2025)
Islamic Religious Education (PAI) in Indonesia is experiencing a significant transformation along with the development of digital technology, which has the potential to introduce local cultural values ??in religious learning. This research aims to examine the role of digital technology in introducing and preserving local culture in Islamic religious education, as well as the challenges faced in its implementation. The research method used is library research by collecting various references and literature related to the application of technology in religious education, integration of local culture, and education policy in Indonesia. The research results show that digital technology, such as game-based applications and interactive learning platforms, can increase student participation in religious learning, introduce local cultural values, and strengthen students' cultural identity. However, the main challenges found were the gap in technology access between urban and rural areas and the quality and relevance of learning content. The implication of this research is the need to develop a curriculum based on local culture which is balanced with improvements in technological infrastructure throughout Indonesia.